Metodologia para uso de simulação física no estudo da ZAC e na obtenção de diagramas CCT para soldagem - Araújo, Douglas Bezerra de (2008)
The joining of metals is often associated to metallurgical problems. Specifically, metallurgical transformations in the HAZ (Heat Affected Zone) can occur, what lead to undesirable microestructural changes. The HAZ is a difficult region for studying due to its small dimensions and high thermal gradientes. Thus, in order to overcome this limitation of the HAZ study, there are in the literature different proposes of HAZ-simulator machines (physical simulation), which uses the Joule effect for heating specific coupons that cool down by conduction and convection. This approach intends to simulate the thermal cycle in a real HAZ obtained in a real welding. However, the use of traditional coupons with cylindrical geometry presents restrictions of portraying the real case, i.e., the welding. In the cylindrical geometry option, the obtained thermal cycles do not present temperature gradients closer to the ones in real weldments. Hence, to overcome this limitation, finite elements modeling was carried out and different coupon geometries were simulated. The objective is to reach thermal cycles as close as possible to the ones obtained in a real situation, for a subsequent physical simulation. This approach showed proper and the physical and numerical present coherent results. The next step is the physical simulation validation by comparing to real weldments. This would be the most intuitive way. However, it was proposed to conduct this validation by determining CCT (Continuous Cooling Transformation) diagrams. This approach has the advantage of reaching important technological results at the same time of validating the physical simulation, since CCD diagrams dedicated to welding are very difficult to find in literature. It is possible to concluded that the physical simulation does represent the HAZ and can be used to build up CCT diagrams